2020
DOI: 10.1071/ch20129
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterisation of Two Lithium Tetramethylberyllate Salts and a Series of β-Diketiminato Beryllium Alkyl Complexes

Abstract: A safer route than that previously published for the synthesis of [BeI2(OEt2)2] has been developed. Reactions of beryllium dihalide complexes [BeX2(OEt2)2] (X=Br or I) with either LiMe or LiBun lead to mixtures of products, which have been shown to act as sources of ‘BeR2’ (R=Me or Bun) in previous synthetic studies. Here, a titration method has been developed to determine the quantity of metal alkyl residues in these ‘BeR2’ mixtures that are available for subsequent alkane elimination reactions. Treating ‘BeM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…However, in a different study on the behaviour of 9 BeBr 2 and 7 BeEt 2 rapid ligand exchange was reported and supported with NMR studies [18] . More recently, mixtures of [(Et 2 O) 2 BeI 2 ] and MeLi or n BuLi were shown to react like “BeR 2 ” (R=Me, n Bu) but are poorly defined in solution [19] . Additionally, there are only three X‐ray crystallographically authenticated beryllium Grignard compounds [20–22] .…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, in a different study on the behaviour of 9 BeBr 2 and 7 BeEt 2 rapid ligand exchange was reported and supported with NMR studies [18] . More recently, mixtures of [(Et 2 O) 2 BeI 2 ] and MeLi or n BuLi were shown to react like “BeR 2 ” (R=Me, n Bu) but are poorly defined in solution [19] . Additionally, there are only three X‐ray crystallographically authenticated beryllium Grignard compounds [20–22] .…”
Section: Introductionmentioning
confidence: 85%
“…[18] More recently, mixtures of [(Et 2 O) 2 BeI 2 ] and MeLi or n BuLi were shown to react like "BeR 2 " (R = Me, n Bu) but are poorly defined in solution. [19] Additionally, there are only three X-ray crystallographically authenticated beryllium Grignard compounds. [20][21][22] As organometallic beryllium chemistry is currently experiencing something of a resurgence, [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] knowledge of Schlenk type equilibria is important for further developments in the field.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the ubiquity of organomagnesium reagents, organoberyllium chemistry is relatively unexplored due, at least in part, to the perceived toxicity of this element. Indeed, although organoberyllium complexes were prepared as early as the 1920s, the field has subsequently been relatively devoid of methodical, fundamental beryllium research. Recently, there has been renewed interest in the organometallic chemistry of beryllium, driven by a desire to understand the biotoxicity mechanisms of this element and exploit its unique electronic properties for chemical transformations. Within the past five years, the first compounds containing formally zero- and monovalent beryllium centers, in addition to the first BeC and BeN bonds have all been reported. …”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown that the type of ether used has significant impact on the reaction outcome [7] . Hence, attempts have been made to synthesize beryllium alkyls in the presence of as few ether molecules as possible [21] or in the total absence of any O ‐donor [20] . However, even though the latter route yields beryllium alkyls, which are completely ether free, they contain trace amounts of phosphines, which are used as solubilizers for the beryllium halide.…”
Section: Introductionmentioning
confidence: 99%